The interaction between dendritic cells and T follicular helper cells drives inflammatory bowel disease: a review - Lv, You; Jin, Yan-Ling; Zhou, Ze; Liao, Jia-Bao; Zhang, Zhu-Quan; Tang, Lin-Yu; Xie, Xue-Hua; Wang, Si; Jin, Meng-Xue; Liu, Hong-Yi (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD), encompassing Crohn’s disease (CD) and ulcerative colitis (UC), has an important pathogenesis that lies in the self-amplifying inflammatory circuit formed by bidirectional interactions between dendritic cells (DCs) and T follicular helper (TFH) cells. This review elucidates that specific mature DC subsets in the intestinal inflammatory microenvironment drive TFH cell differentiation through synergistic co-stimulatory signals (CD80/CD86-CD28, OX40L-OX40) and cytokine networks (IL-12/STAT4/BCL-6, TGF-β/c-Maf/CXCR5); conversely, TFH-derived Lymphotoxin alpha 1 beta 2 (LTα1β2) activates stromal cell LTβR/NF-κB signaling pathway, inducing chemokine (CXCL13, CCL19, CCL21) production, thereby recruiting CCR7+ DC and CXCR5+ lymphocytes to form structural lymphoid clusters. Within these clusters, sustained DC-TFH cell interactions enhance TFH pathological effector functions (e.g., excessive IL-21 secretion), promote Th1/Th17 differentiation and weaken regulatory T cell inhibitory capacity, ultimately causing barrier destruction and tissue damage. Notably, while this pathogenic axis is active in both CD and UC, its cellular dynamics and microenvironment may exhibit disease-subtype distinctions. Current therapeutic strategies targeting this axis—including JAK inhibitors (e.g., upadacitinib), cytokine biologics (e.g., ustekinumab) and integrin blockers (e.g., vedolizumab)—achieve efficacy by interfering with DC-dependent TFH differentiation or TFH-mediated DC aggregation. Emerging evidence indicates traditional Chinese medicine active components (e.g., ginsenoside Rh2, curcumin) may intervene in this interaction through multi-pathway immunoregulation. However, utilizing single-cell and spatial transcriptomics to analyze spatial characteristics and disease-subtype-specific profiles of DC-TFH cell interactions remains key to developing next-generation therapies. While this axis provides a novel perspective for understanding immune dysregulation in IBD, its temporal role in disease initiation, crosstalk with other immune pathways, and translation from animal models to human disease remain challenges and future directions for the field.